2016
DOI: 10.1080/09168451.2015.1069696
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-binding modules influence substrate specificity of an endoglucanase from Clostridium thermocellum

Abstract: Most cellulases contain carbohydrate-binding modules (CBMs) that largely contribute to their activity for insoluble substrates. Clostridium thermocellum Cel5E is an endoglucanase having xylanolytic activity. The Cel5E originally has a family 11 CBM preferentially binding to β-1,4- and β-1,3-1,4-mixed linkage glucans. In this study, we replaced the CBM with a different type of CBM, either a family 3 microcrystalline cellulose-directed CBM from Clostridium josui scaffoldin, or a family 6 xylan-directed CBM from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…However, despite the higher affinity for barley β-glucan, we did not observe an increase of activity of the chimeric enzyme for this substrate. This evidence is supported by other studies 22 , 23 , where higher enzyme activities on a specific substrate did not correlate with the binding amounts for that substrate. On the contrary, it seems that the highest activity is correlated with a moderate binding affinity of the CBM.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…However, despite the higher affinity for barley β-glucan, we did not observe an increase of activity of the chimeric enzyme for this substrate. This evidence is supported by other studies 22 , 23 , where higher enzyme activities on a specific substrate did not correlate with the binding amounts for that substrate. On the contrary, it seems that the highest activity is correlated with a moderate binding affinity of the CBM.…”
Section: Resultssupporting
confidence: 85%
“…The increase of activity on insoluble rather than soluble substrates is a common trait of many CBMs 11 . Other studies reported the ability of Ct CBM11 to increase the activity of GH5 catalytic domain of CtCelH against the insoluble substrate Avicel but not against soluble substrates such as lichenan and carboxymethyl cellulose (CMC) 22 , 26 , and the absence of CBM reduced the activity of CtCel5E on Avicel, ball-milled cellulose and oat-spelt xylan compared with its CBM containing forms (wild type or CBM3 and CBM6 chimeras) 22 .…”
Section: Resultsmentioning
confidence: 99%
“…In one example, the preference of a bacterial fructosidase for either branched or linear fructan polysaccharides could be modulated by the inclusion of a CBM66 domain that binds terminal fructofuranose residues, facilitating enzyme targeting of branching structures [58]. Few examples in the literature describe a CBM that altered the specificity of a partner GH to such an extent that a different linkage would be preferentially cleaved, although changing the binding specificity of the CBM appended to endo‐ glucanases and acetyl esterases can result in altered activity on complex biomass substrates [55,59,60].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has shown that hydrolytic activities of multifunctional CelE toward cellulose, lichenan, xylan and mannan increased by more than 200% when the catalytic domain was recombinantly fused with different CBMs having corresponding binding specificities (Walker et al 2015 ). Another example also demonstrated that catalytic activities of multifunctional endoglucanase, Cel5E, toward oat-spelt xylan, ball-milled cellulose and microcrystalline cellulose increased by 150%, 900% and 200% when fused with CBM6, CBM11 and CBM3, respectively, which target corresponding substrates (Ichikawa et al 2016 ). As Type III and IV CBMs prefer to bind branched substrates, fusion of those CBMs to main-chain degrading enzymes is probably able to dominate the degradation of decorated polysaccharides directly.…”
Section: Resultsmentioning
confidence: 99%